Molecular response after obinutuzumab plus high-dose cytarabine induction for transplant-eligible patients with untreated mantle cell lymphoma (LyMa-101): a phase 2 trial of the LYSA group. Issue 11 (November 2020) - Le Gouill, Steven; Beldi-Ferchiou, Asma; Alcantara, Marion; Cacheux, Victoria; Safar, Violaine; Burroni, Barbara; Guidez, Stéphanie; Gastinne, Thomas; Canioni, Danielle; Thieblemont, Catherine; Maisonneuve, Hervé; Bodet-Milin, Caroline; et al.
Summary: Background: Obinutuzumab monotherapy has shown promising efficacy in mantle cell lymphoma. We aimed to investigate the activity of obinutuzumab plus DHAP (dexamethasone, high-dose cytarabine, and cisplatin), measured by minimal residual disease quantitative (q)PCR status in the bone marrow after four cycles. Methods: LyMa-101 was a prospective, open-label, single-arm, phase 2 trial. Participants were enrolled from 28 hospitals in France. Newly diagnosed patients with mantle cell lymphoma (aged 18 to <66 years) who were eligible for autologous stem-cell transplantation received four cycles of obinutuzumab plus DHAP (obinutuzumab 1000 mg/m 2 intravenously on days 1, 8, and 15 at cycle 1 and day 1 at cycles 2, 3, and 4; dexamethasone 40 mg intravenously on days 1–4, cytarabine 2 g/m 2 intravenously every 12 h on day 1, and according to local investigator, cisplatin 100 mg/m 2 by continuous infusion over 24 h on day 1 or carboplatin area under the curve 5 or oxaliplatin 130 mg/m 2 ) every 21 days before transplantation, and 3 years of obinutuzumab (1000 mg/m 2 every 2 months) maintenance followed by minimal residual disease-based obinutuzumab on-demand maintenance. The primary outcome was minimal residual disease negativity in the bone marrow after four cycles of obinutuzumab plus DHAP at the end of induction, measured in the efficacy set (all minimal residual disease-informative [bone marrow or peripheral blood] patients who received at least one dose of obinutuzumab). Obinutuzumab plus DHAP was considered effective if bone marrow minimal residual disease negativity was 70% or more by intention to treat. The trial is closed to recruitment and registered with ClinicalTrials.gov, NCT02896582 . Findings: 86 patients were enrolled between Nov 29, 2016, and May 2, 2018. 81 patients completed induction, 73 underwent autologous stem-cell transplantation, and 69 started maintenance therapy. 55 (75%) of 73 patients in the efficacy set reached minimal residual disease negativity in bone marrow at end of induction. According to the protocol definition, 18 (25%) of 73 patients in the efficacy set were minimal residual disease-positive: 12 patients who were minimal residual disease-positive in the bone marrow, plus two patients who progressed during induction, and four patients who did not have minimal residual disease assessment. The most common grade 3–4 treatment-emergent adverse events were anaemia (grade 3, 26 [31%] of 85 patients; grade 4, three [4%] of 85 patients) and neutropenia (grade 3, 13 [15%] of 85 patients; grade 4, 32 [38%] of 85 patients). 58 serious adverse events occurred during the induction phase. There were no treatment-related deaths. Interpretation: Obinutuzumab plus DHAP is a well tolerated regimen and has good activity for inducing minimal residual disease negativity in the bone marrow of transplant-eligible patients with mantle cell lymphoma. Obinutuzumab plus DHAP has potential activity as induction chemotherapy, with bone marrow minimal residual disease negativity potentially predicting long-term disease control. Funding: Roche SAS.